2014
DOI: 10.1002/2013gl058084
|View full text |Cite
|
Sign up to set email alerts
|

A signal of persistent Atlantic multidecadal variability in Arctic sea ice

Abstract: Satellite data suggest an Arctic sea ice-climate system in rapid transformation, yet its long-term natural modes of variability are poorly known. Here we integrate and synthesize a set of multicentury historical records of Atlantic Arctic sea ice, supplemented with high-resolution paleoproxy records, each reflecting primarily winter/spring sea ice conditions. We establish a signal of pervasive and persistent multidecadal (~60-90 year) fluctuations that is most pronounced in the Greenland Sea and weakens furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 43 publications
(72 reference statements)
10
85
0
Order By: Relevance
“…This thickening of ice in the Beaufort sea is linked to a low pressure center over the Arctic in the LMR, which is not present in the CCSM4 prior (or in other reanalyses of the instrumental period). Sea ice retreat coincident with the positive phase of the AMO has also been shown in model-based studies (see, e.g., Miles et al, 2014). Such retreat and thinning of sea ice is also consistent with increased ocean heat transport into the North Atlantic, possibly due to strengthening of the AMOC during the positive phase of the AMO (considered further in Sect.…”
Section: Thermodynamics Of the Amo In The Lmrsupporting
confidence: 71%
See 2 more Smart Citations
“…This thickening of ice in the Beaufort sea is linked to a low pressure center over the Arctic in the LMR, which is not present in the CCSM4 prior (or in other reanalyses of the instrumental period). Sea ice retreat coincident with the positive phase of the AMO has also been shown in model-based studies (see, e.g., Miles et al, 2014). Such retreat and thinning of sea ice is also consistent with increased ocean heat transport into the North Atlantic, possibly due to strengthening of the AMOC during the positive phase of the AMO (considered further in Sect.…”
Section: Thermodynamics Of the Amo In The Lmrsupporting
confidence: 71%
“…We find that a positive AMO index coincides with warmer continents, a two-lobed pattern of warming over the Atlantic, and a warmer Arctic (Kushnir, 1994;Delworth and Mann, 2000;Chylek et al, 2009). In the Arctic, sea ice retreats from the Greenland, Iceland, and Nordic seas and thins over much of the Arctic Ocean (Miles et al, 2014). Globally, precipitation increases and the ITCZ strengthens and shifts northward (Knight et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both modeling results (31,32) and multicentury historical records (33) showed that winter Arctic sea ice variability is closely linked to the AMV. The AMOC is suggested to have strengthened since the mid 1970s as implied indirectly by its fingerprints (34,35).…”
mentioning
confidence: 94%
“…Also, an increasing Atlantic water inflow to the eastern Arctic (Polyakov et al, 2012) is another heat source, that may reach the ice through various mixing mechanisms (Carmack et al, 2015). Variability in Atlantic water in the Arctic may be related to the Atlantic Multidecadal Oscillation and a similar period of oscillation in the sea-ice pack (Miles et al, 2014). Heat released from the Atlantic water has recently been identified as a significant contributor to sea-ice loss (Polyakov et al, 2017).…”
Section: Positive Feedbacksmentioning
confidence: 99%